The Application of MathCityMap at SDN Kaweron II to Improve Students' Problem Solving Abilities - Khoir, Ani Kholifatul (FKIP Universitas Muhammadiyah Tangerang, 2024)
Quality education is one of the rights that every citizen must obtain. The quality of education can be seen through the learning process provided by teachers to students at school. However, when the Covid-19 pandemic hit, the learning process became very hampered, especially in mathematics learning. This cannot be separated from the assumption that mathematics is a subject that is difficult for students to understand. The presence of the MathCityMap application is one of the innovations in the field of mathematics learning because it can make learning mathematics more fun for students. This paper aims to analyze the MathCityMap experiment at SDN Kaweron II with the aim of improving students' problem solving abilities. The research results show that using MathCityMap is quite effective in improving students' problem solving abilities because learning is packaged in a fun way and attracts students' interest in studying mathematics outside the classroom. Using MathCityMap also becomes a challenge for students to want to solve every problem given by the teacher. Therefore, apart from problem solving skills, this learning also improves students' critical thinking and teamwork skills.